2019
DOI: 10.1186/s12882-019-1261-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentrations of platelet- and endothelial-derived microparticles in patients with myocardial infarction and reduced renal function- a descriptive study

Abstract: Background Patients with chronic kidney disease (CKD) have a high risk of recurring thrombotic events following acute myocardial infarction (AMI). Microparticles (MPs) are circulating small vesicles shed from various cells. Platelet microparticles (PMPs) reflect platelet activation and endothelial microparticles (EMPs) reflect endothelial activation or dysfunction. Both increase following AMI, and may mediate important biological effects. We hypothesized that AMI patients with CKD have further ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…They also correlated positively to peak hs‐troponin levels and inversely to LVEF, suggesting a direct correlation to injury severity. These findings are in general agreement with previous data showing increased numbers of platelet‐ and endothelial‐derived EVs in patients with ACS, possibly reflecting the formation of coronary thrombotic occlusions, compared to patients with chronic CAD and healthy individuals 12‐23 . We also found an increase in SSEA‐4, an antigen expressed by ‘very‐small embryonic‐like stem cells’ that are mobilized from bone marrow after cardiac ischemia and participate in endothelial repair, 33 at 24‐48 hours in STEMI patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also correlated positively to peak hs‐troponin levels and inversely to LVEF, suggesting a direct correlation to injury severity. These findings are in general agreement with previous data showing increased numbers of platelet‐ and endothelial‐derived EVs in patients with ACS, possibly reflecting the formation of coronary thrombotic occlusions, compared to patients with chronic CAD and healthy individuals 12‐23 . We also found an increase in SSEA‐4, an antigen expressed by ‘very‐small embryonic‐like stem cells’ that are mobilized from bone marrow after cardiac ischemia and participate in endothelial repair, 33 at 24‐48 hours in STEMI patients.…”
Section: Discussionsupporting
confidence: 92%
“…Most circulating EVs in healthy individuals are derived from platelets and erythrocytes; however, vesicles also are released from leucocytes, endothelial cells, monocytes, neutrophils and lymphocytes 7,11 . Previous studies have shown increased numbers of platelet, endothelial cell‐ and leucocyte‐derived EVs in patients with acute coronary syndromes (ACS) or chronic CAD 12‐23 . However, partially divergent results have been reported, in part due to methodological differences in EV isolation 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Concentration of CD40 ligand + PMPs is positively associated with severity of CKD and inversely correlated with eGFR [35] Circulating sCD40L and sCD40…”
Section: Disease Condition Presence Of Cd40/cd40l Associations With Kmentioning
confidence: 97%
“…Platelet-derived microparticles (PMPs) are the most abundant microparticles in circulation and increased PMPs are associated with diabetes mellitus, myocardial infarction, and CKD [31][32][33][34]. Mörtberg and colleagues have recently shown that circulating concentrations of PMPs expressing CD40 ligand were positively associated with the severity of chronic kidney disease, and the concentration of CD40 ligand + PMPs is inversely correlated with estimated glomerular filtration rate (eGFR) [35]. In other studies, CD40 ligand + PMPs of CKD patients can be reduced by the vitamin D2 derivative, paricalcitol [36], or lipid-lowering treatment (LLT) with simvastatin in the settings of diabetes mellitus (DM)-CKD [34].…”
Section: Cd40 and Cd40l As Markers Of Renal Function In Kidney Diseasementioning
confidence: 99%
“…In uremic conditions, it was demonstrated that PCS, IS, and inorganic phosphate induced the formation of EMPs from endothelial cells [ 113 , 163 , 167 , 168 , 169 ]. Studies have also shown that EMPs are related to endothelial dysfunction in CKD patients [ 17 , 167 , 170 , 171 ]. In vitro, Carmona et al [ 163 ] showed that EMPs from endothelial cells exposed to IS had increased levels of ICAM-1 and PECAM-1, and miRNAs (e.g., miR-181a-5p, miR-4454, and miR-150-5p).…”
Section: Uremic Toxins Induce the Formation Of Endothelial Micropamentioning
confidence: 99%